Organizational behavior human behavior at work - Newstrom, John W.; Davis, Keith (McGraw-Hill Irwin, 2002)
"Organizational Behavior: Human Behavior at Work, 11e", was originally created 45 years ago by Keith Davis. This solid research-based and referenced text is known for its very readable style and innovative pedagogy. While minimizing technical jargon, Newstrom and Davis carefully blend theory with practice so that its basic theories come to life in a realistic context. As in previous editions, this edition will be filled with practical, applied advice.